Chloroquine and hydroxychloroquine maculopathy: a review of diagnostic and therapeutic guidelines in Hungarian and international clinical practice - Fodor, Mariann; Lukács, Miklós Ágoston; Szekanecz, Zoltán; Nagy, Zoltán Zsolt (Orvosi hetilap, 2024)
Drugs belonging to the aminoquinoline class have been used for a long time and are indispensable in the therapy of several pathologies, especially in systemic inflammatory diseases. The retinal toxicity affecting central vision caused by the use of chloroquine or hydroxychloroquine has been well-known already in the past century. Ophthalmic screening of patients who are taking these drugs is a frequently discussed issue, which manifests in constantly renewed screening protocols. In this study, we review the currently used international recommendations and the new data that provided the basis for the applied changes in these protocols. Devices used in a state-of-the-art ophthalmic screening (automatic visual field test, optical coherence tomography [OCT], fundus autofluorescence [FAF], multifocal electroretinography [mfERG]) are also presented as well as all risk factors, which make patients vulnerable to retinal toxicity. Finally, we introduce a screening protocol that is best suited to Hungarian health care. Orv Hetil. 2024; 165(30): 1147–1153.